Indikator Praktik Sehat secara Mental pada Lanjut Usia berdasarkan Dukungan Sosia Keluarga (Studi Kualitatif di Kabupaten Lumajang) (Practical Indicators of Healthy Mental at Elderly based on Family Support (Qualitative Study in Lumajang Regency)) - Desy Iswari amalia; Elfian Zulkarnain; Novia Luthviatin (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
AbstractThe increase of Life Expectancy Age (UHH) at birth, caused a significant increased in the number of elderly people in the future. Problems which related to mental health were problems that were strongly associated with the elderly. Physical or non physical needs of the elderly were more secure if the elderly lived with the family. health indicators were very important and very helpful to monitor the development of elderly health and to prevent disease incidence. This study aimed to analyze indicators of mental health practices in the elderly based on social support from the family. The studi using explorative research with qualitative approach. Indicators of health practice mentally in the elderly based on family social support, they included: the practice of developing hobbies and interests of the elderly, the practice of recreation periodic basis, the practice of looking attractive, the practice of maintaining memory, the practice of keeping the confidence the practice of attractive, practical tackle complex problems, the practice of visiting the ancestral grave, the practice of accepting the release of office during retirement, the practice of adjusting from the death of a spouse, reconciliation practices not to regret adverse events in the past, the practice of giving parents education system and adoption by children. The practice of establishing loyalty with spouses, the practice of maintaining harmony in-law relationship with the daughter-in-law, the practice of establishing closeness with grandchildren.Keywords: Healthy, healthy mental, elderly, family social support